Ancestral iconicity: the dance language of bees revisited. - Schlenker,P; Lamberton,J; Lan,N; Lamberton,J; Geraci,C; Salis,A; Ravaux,L; Grüter,C; Ryder,RJ; Chemla,E (Biol Rev Camb Philos Soc, 2026)
The waggle dance of bees has given rise to some of the most striking and detailed studies of animal communication. But because of its gradient character, the waggle dance has widely been taken to have properties that are wholly distinct from those of human language. We argue that this is mistaken, and that the waggle dance represents the oldest instantiation of an iconic system also found in human language, notably in sign language. The waggle dance helps bees locate a food source through four properties: (1) food distance is conveyed through the duration of the waggling phase; and (2) food direction is conveyed through the orientation of the waggle run. In addition, (3) while in bees that dance horizontally, the waggle run points towards the food source, in bees that dance vertically the information involves transposition: the angle of the dance relative to 'upwards' is interpreted as the angle of the food direction relative to the sun. Finally, (4) the number of waggle runs increases with food quality. We show that properties 1 and 2 are instantiated in sign language classifier predicates, highly iconic constructions that produce visual animations of the orientation and movement of an entity. Furthermore, classifier movement (property 3) can be interpreted either directly or with 'viewpoint shift', a more flexible version of transposition. Property 4 seems to be instantiated more generally in the pragmatics of human and animal communication, as repetition can convey intensification and/or excitement (e.g. Go, go, go!). We further show experimentally that properties 1-3 are instantiated in some gestures understood by non-signers. Thus the waggle dance is a primitive form of a semantic system also found (through convergent evolution) in human language. It is remarkably ancient, at least 20 million years old according to phylogenetic reconstructions. While the horizontal dance (without transposition) is usually thought to be ancestral, a closer look at extant phyloge